Electron microscopic evaluation of quality tooling of curved root canals of molars - A. V. Arutyunov (Кубанский научный медицинский вестник, 2015)
The article presents the results of a study of 155 root canals of molars removed the upper and lower jaws, of whom 620 made of thin sections for scanning electron microscopy studies. As the results of the study, an increase in the curvature of the root canals of molars in the bucco-lingual and mediodistal directions by more than 25°, significantly reduces the quality of the tooling. Taking into account individual features of architectonic root canals, endodontic instruments expand the range and improve its cutting efficiency will ensure higher quality tooling.